Regulasi Diri dan Makna Hidup pada Mahasiswa Penghafal Al-Qur’an di Rumah Tahfidz Yatim Dhuafa Palembang - Paulina, Melisa; Istiningtyas, Listya; Lukmawati, Lukmawati (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
This study aims to determine self-regulation and the meaning of life of UIN Raden Fatah students in memorizing Qur’an at the Tahfidz Yatim Dhuafa House Palembang. With qualitative research phenomenological design and using 3 subjects who have memorized 30 Juzs. Data analysis was performed with a coding system. Data validity was carried out by extending participation and triangulation. Based on the results of research and discussion, it can be concluded that the results of this study of Al-Qur'an reciters have good self-regulation and find the meaning of life from memorizing Al-Qur'an. The three subjects balance themselves and manage time in carrying out daily routines such as lectures, teaching, and memorizing the Qur'an. In overcoming obstacles, they always maintain their motivation to stay enthusiastic in memorizing the Al-Qur'an. The three subjects apply what they have memorized, and maintain their behavior so that they always do good and have good morals.